The Influence of Knowledge and Security on The Decision To Use GPN Debit Cards - Alfian, Ian Ian; Binti Abu Hasan, Nurul Widad (Journal of Islamic Financial Technology, 2023)
The purpose of this study is to determine the influence of knowledge and security on the decision to use GPN debit cards for students of the Sharia Banking Study Program IAIN Padangsidimpuan. The discussion of this research is related to the field of marketing management science so the approach taken is theories related to knowing product safety. The type of research used is quantitative field research. The sample used in this study was 92 respondents. Sampling techniques using purposive samples, and data collection techniques used are interviews, documentation, and questionnaires. The analysis used is a validity test, reliability test, basic assumption test (normality test), classical assumption test (multicollinearity test and heteroskedasticity test), multiple linear regression test, hypothesis test, namely coefficient of determination (R Square), partial test (t test), simultaneous test (F test) and using SPSS software version 26.The results showed that knowledge variables had a positive and insignificant effect on the decision to use GPN debit cards in terms of t calculate t table (1.489 1.66216). Security variables have a positive and significant effect on the decision to use GPN debit cards as seen from the t table (6.807 1.66216). There is a positive influence of knowledge and security on the decision to use GPN debit cards indicated by the value of Fcalculate Ftable (119.064 2.36). The coefficient of determination (R2) shows that knowledge and security variables influence the decision variable to use GPN debit cards by 72% and the remaining 28% is explained by other variables not studied in this study.